EFFICIENCY OF ANTIVIRAL THERAPY OF CHRONIC HEPATITIS C DEPENDING ON GENE POLYMORPHISMS OF CYP2E1 - Годован, В.В.; Остапчук, К.В. (World of Medicine and Biology, 2014)
The effect of CYP2E1 gene polymorphisms on the efficiency of the treatment of chronic hepatitis C by peginterferon+ribavirin was stadied in 33 patients. Among them genotype DD by polymorphism CYP2E1*6 had 24 (72,7 %) patients, genotype CD - 9 (27,3%) patients. Genotype CC was not revealed. Patients with genotype CD more often had early and rapid virological responses compared to the patients with genotype DD (respectively 88,9% and 45,8 %, p = 0,026). Patients with genotype CD restored the level of serum alanine aminotransferase faster (after 12 weeks of treatment) than the patients with genotype DD. Treatment of the patients with chronic hepatitis C with peginterferon and ribavirin was more effective if they had genotype CD.